Valuasi Ekonomi Wilayah Adat Taman Sunsong Kabupaten Sekadau - Stefanus Masiun; Lorensius Tobing (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This article aims to investigate the valuation of the indigenous territory of Taman Sunsong in Sekadau Regency, with a focus on uncovering the cultural, economic, and environmental values inherent in the Taman Sunsong Indigenous Community. The research employs a mixed-method approach, combining qualitative and quantitative methods. Field surveys were conducted to gather data on the social, cultural, and economic profiles of the indigenous community. In-depth interviews were carried out with traditional leaders and community members to gain a comprehensive understanding. Economic data was collected through surveys, market price approaches, and benefit transfer methods. The findings reveal that the Taman Sunsong Indigenous Community possesses unique cultural traits and a way of life governed by customary values, rituals, and religious practices. Their social life is rooted in strong communal interactions, while a close relationship with the surrounding environment also plays a significant role. The significance of preserving nature and culture is evident in the high value placed on the indigenous forest. The forest holds cultural significance and profound knowledge about ecosystem balance and sustainable resource utilization. The economy of the Taman Sunsong indigenous region relies on fields, gardens, traditional craftsmanship, and the potential for ecotourism. To assess the economic value of the indigenous territory, market price approaches and benefit transfer methods are employed. Market prices are used to gauge the value of agricultural commodities and forest products. The benefit transfer method is utilized to estimate the value of environmental services such as oxygen production by the forest.